Evaluation of competition strategies applied in logistics management during the pandemic process: A research on logistics companies in Istanbul - Akkartal, Gonca Reyhan; Çulhaoğlu Uludağ, Candide (ACC Publishing, 2022)
This study aims to determine the changes in the changing competition, growth, and customer strategies within the scope of the logistics management of the COVID-19 process that affects the whole world. The study will be carried out in the form of an interview, and it will be evaluated how the changes in the supply chain processes during the pandemic process reflect on the competition, growth, and customer strategies business basis. According to the results, recommendations will be made to companies operating in the logistics sector in parallel with the changes in competition, growth, and customer strategies. The study results include the need for speed, digitization, improving the quality of customer relationships, working from home, and expanding e-commerce to create a competitive advantage.

Bu çalışmanın amacı, tüm dünyayı etkisi altına alan COVİD -19 sürecinin lojistik yönetimi kapsamında değişen rekabet, büyüme ve müşteri stratejilerinde meydana gelen değişimleri belirlemektir. Çalışma görüşme şeklinde gerçekleştirilecek olup, pandemi sürecinde tedarik zinciri süreçlerinde yaşanan değişimlerin iş bazında rekabet, büyüme ve müşteri stratejilerine nasıl yansıdığı değerlendirilecektir. Elde edilen sonuçlara göre rekabet, büyüme ve müşteri stratejilerindeki değişimlere paralel olarak lojistik sektöründe faaliyet gösteren firmalara önerilerde bulunulacaktır. Çalışma sonuçları, rekabet avantajı yaratmak için hız, dijitalleşme, müşteri ilişkilerinin kalitesinin arttırılması, evden çalışma ve e-ticaretin genişlemesi gerekliliğini içerir.
Pandemi sürecinde lojistik yönetiminde uygulanan rekabet stratejilerinin değerlendirilmesi: İstanbul'daki lojistik firmaları üzerine bir araştırma
Keywords: Logistics; Supply Chain Management; Strategic Management; Lojistik; Tedarik Zinciri Yönetimi; Stratejik Yönetim